1998
DOI: 10.1080/03079459808419323
|View full text |Cite
|
Sign up to set email alerts
|

Growth analysis of adenoviruses isolated from pigeons in chicken cells and serological characterization of the isolates

Abstract: The susceptibility of chicken embryo liver (CEL) and chicken kidney (CK) cells to eight adenoviruses isolated from different pigeons were investigated. Isolation and propagation was most successful in CEL cells. The cytopathic effect, i.e. cell rounding and detachment of the cells was typical for adenoviruses. Titres of up to 10(6.6) plaque-forming units/ml could be reached on CEL cells. Transferring CEL-grown virus onto CK cells also resulted in a cytopathic effect but with much lower titres, whereas the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Such molecular techniques have proved to be effective and common for identification of new viruses in recent times; nevertheless, a definitive diagnosis of viral infection has relied upon virus isolation. Although the use of a homologous cell culture system was reported to be preferable (McFerran & Adair, 2003), avian adenoviruses have also been isolated successfully from different species of birds using chicken cells (McFerran et al, 1976;Gassmann et al, 1981;Bouquet et al, 1982;Hess et al, 1998;Vereecken et al, 1998). In the present study the suspicion of adenovirus infection was confirmed by electron microscopic examination.…”
Section: Discussionsupporting
confidence: 64%
“…Such molecular techniques have proved to be effective and common for identification of new viruses in recent times; nevertheless, a definitive diagnosis of viral infection has relied upon virus isolation. Although the use of a homologous cell culture system was reported to be preferable (McFerran & Adair, 2003), avian adenoviruses have also been isolated successfully from different species of birds using chicken cells (McFerran et al, 1976;Gassmann et al, 1981;Bouquet et al, 1982;Hess et al, 1998;Vereecken et al, 1998). In the present study the suspicion of adenovirus infection was confirmed by electron microscopic examination.…”
Section: Discussionsupporting
confidence: 64%
“…The first distinct pigeon AdV strain was reported by Hess et al (1998). On chicken embryo liver cells, they isolated a virus that was found to be a serologically novel type.…”
mentioning
confidence: 99%
“…As to wild birds, aviadenoviruses have been found in representatives of the orders Falconiformes (Schrenzel et al, 2005), Psittaciformes (Raue et al, 2005a;Wellehan et al, 2005) and Charadriiformes (Bodewes et al, 2013). From Columbiformes, a single AdV named pigeon adenovirus 1 (PiAdV-1), has been characterised by DNA sequence (Hess et al, 1998;Marek et al, 2014b).…”
mentioning
confidence: 99%
“…They have been grouped into 12 serotypes (FAdV-1 to -8a and -8b to -11) based on cross-neutralization test (Hess, 2000), and at least 12 genotypes within the five species have been revealed by sequence analysis of the hexon loop 1 (L1) gene region (Marek et al, 2010a). Several additional aviadenoviruses have been isolated from or detected in hosts other than chicken such as turkey, goose, duck, pigeon and different falcon and psittacine species (Adair & Fitzgerald, 2008;Hess et al, 1998;Raue et al, 2005;Schrenzel et al, 2005;Smyth & McNulty, 2008;Wellehan et al, 2005). For the classification of these non-chicken AdVs, some species are already recognized within the genus Aviadenovirus and some represent candidate species in the genus.…”
Section: Introductionmentioning
confidence: 99%